Sistema semi-intrusivo de monitoramento de energia elétrica residencial - Guilmo, João Antonio (2021)
Electricity monitoring is an important process, from generation, transmission, and distribution, to the final consumer. It allows the monitoring system to have valuable data about the su- pervising process, assisting in decision-making. This study aims to develop a semi-intrusive system for acquiring and verifying electricity consumption. The system comprises hardware to get data and software for processing, storage, and creating the supervision system. The ESP32 microcontroller is used to carry out the work. The supervisory system is built using the Home Assistant Operating System, which is generally used for home automation. Data storage is performed using the own Home Assistant. This monitoring system allows and helps the consumer identify trends in energy consumption, aiding in decision making. The developed system monitors the voltages of the two phases and the current of two circuits; the entire circuit is tested in a two-phase residential distribution board and the loads used are common household appliances such as minibars, fans, computers, and lamps. The results were acceptable regarding the information of the loads tested.